Dietary ascorbic acid requirement for growth of striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878) juveniles. (18th August 2017) - Daniel, N.; Muralidhar, A.P.; Srivastava, P.P.; Jain, K.K.; Pani Prasad, K.; Manish, J.; Sivaramakrishnan, T.
Abstract: A sixty‐day feeding trial was conducted to determine the ascorbic acid (AA) requirement for growth of striped catfish, Pangasianodon hypophthalmus juveniles. Seven iso‐nitrogenous and iso‐energetic (370 g protein per kg and 19.6 MJ/kg) purified diets were prepared with different levels of ascorbic acid such as control (0), T1 (17.5), T2 (35), T3 (70), T4 (175), T5 (350) and T6 (700) mg ascorbic acid (L‐ascorbyl‐2‐polyphosphate) equivalent per kg diet. Fish with a mean body weight of 3.2–3.4 g were stocked (fifteen fish per tank) in triplicates following a completely randomized design. Each group was fed to satiation twice a day for 60 days. Significant differences were observed in growth, survival, body composition and metabolic enzymes activities with different dietary ascorbic acid levels. Maximum weight gain, specific growth rate (SGR) and protein efficiency ratio (PER) were found in fishes fed with 35 mg AA per kg diet, supported by best feed conversion. Fish fed a diet containing vitamin C had the highest activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) compared to those fed with vitamin C‐depleted diets. In this study, based on using broken‐line regression analysis, the dietary vitamin C requirement for growth of P. hypophthalmus juveniles was estimated to be in the range of 46–76 mg AA per kg, depending on the criterion used, growth and liver storage. Our results will be helpful for the formulation of cost‐effective ascorbic acid incorporated diets for striped catfish, P. hypophthalmus .